Differences in the pharmacokinetics and steady-state blood concentrations of orally administered lenvatinib in adult and juvenile rats - Du, Xiaoyue; Cai, Hongxin; Jin, Nan; Wu, Zhiguo; Wang, Lele; Wang, Zeyu; Xie, Baogang (Frontiers in Pharmacology, 2023)
Objective: The aim of this study was to compare the pharmacokinetics and steady-state serum concentrations of lenvatinib in adult and juvenile rats. Experimental study: An ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) method was developed to quantify lenvatinib in the serum and liver of rats. Six juvenile and six adult rats in each group were orally administered with a single dose of 7.0 mg/kg lenvatinib suspension for pharmacokinetics. Another 12 juvenile and adult rats were subjected to oral gavage with 7.0 mg/kg lenvatinib once daily for 5 days. Biofluild samples were pre-treated by protein precipitation and sorafenib was used as the internal standard for UPLC-MS analysis. The pharmacokinetic parameters were estimated by compartment and statistical model. The mRNA expression of CYP3A2 and SLC22A1 in liver of adult and juvenile rats was measured by real-time fluorescence quantitative PCR (RT-qPCR). Results: The UPLC-MS method met the requirements for quantitative analysis of lenvatinib in serum and liver. The pharmacokinetic results showed that the mean retention time (MRT(0-∞)) was 19.64 ± 7.64 h and 126.38 ± 130.18 h, with AUC(0-∞) values of 3.97 ± 0.73 μg‧mL-1 h and 5.95 ± 2.27 μg mL-1 h in adult and juvenile rats, respectively. When comparing adult rats (0.35 ± 0.15 μg/mL) to juvenile rats, no significant differences were observed in steady-state serum lenvatinib (0.32 ± 0.11 μg/mL), but a noteworthy decrease to one-third of steady-state liver lenvatinib was observed after multiple oral doses of lenvatinib in juvenile rats. Additional findings revealed that the mRNA expression of CYP3A2 and SLC22A1 was notably increased by 6.86 and 14.67 times, respectively, in juvenile rats compared to adult rats. Conclusion: Juvenile rats exhibit lower levels of lenvatinib in the liver’s steady-state, potentially due to the disparity in CYP3A2 mRNA expression. These results imply that the dosage of lenvatinib for pediatric patients may need to be augmented in order to attain the desired clinical outcome.